Delayed Granulocyte Colony-Stimulating Factor (G-CSF) Administration after Chemotherapy Reduces Total G-CSF Doses without Affecting Neutrophil Recovery in a Randomized Clinical Study in Children with Solid Tumors. (16th November 2020) - Yankelevich, Maxim; Hoogstra, David J.; Abrams, Judith; Chu, Roland; Bhambhani, Kanta; Taub, Jeffrey W.
Abstract: The use of G-CSF after myelotoxic chemotherapy accelerates neutrophil recovery reducing the risk of febrile neutropenia. Current guidelines recommend initiating G-CSF 24 hours after myelotoxic chemotherapy. However, the optimal timing of post-chemotherapy G-CSF administration has not been elucidated. Our previous work in murine models demonstrated that the reappearance of myeloid progenitors does not occur in bone marrow until 3–4 days after completion of chemotherapy suggesting that delayed G-CSF administration may be equally efficacious compared to current practice. We conducted a prospective, randomized, crossover study to compare the absolute neutrophil count (ANC) recovery after chemotherapy and a delayed G-CSF administration to a standard G-CSF administration schedule with early G-CSF start. A total of 21 children with solid tumors who received 2 identical cycles of myelotoxic chemotherapy were randomized to start receiving G-CSF either 24 hours after completion of chemotherapy or on the day that their ANC dropped below 1, 000/mm 3 . There was no significant difference in the time to neutrophil recovery (ANC > 1, 000/mm 3 post nadir) between the two G-CSF administration schedules: 16.0 ± 0.5 days in the standard group compared to 16.7 ± 0.4 days in the delayed group (p = 0.36). The total number of G-CSF doses given, however, was significantly less in the delayed group: 6.7 ± 0.6 compared to 10.5 ± 0.6 doses in the standard group (p < 0.0001). Our data show that a delayed administration of post chemotherapy G-CSF resulted in a significant reduction in the number of G-CSF injections without compromising the G-CSF effects on neutrophil recovery.